2017
DOI: 10.1007/s00436-016-5368-8
|View full text |Cite
|
Sign up to set email alerts
|

Status of babesiosis among domestic herbivores in Iran: a systematic review and meta-analysis

Abstract: Babesiosis is a protozoal disease caused by Babesia spp. in mammals and humans worldwide. It is one of the most important tick-borne diseases, which affects livestock productions, reproductions, and accordingly failing economy. In this, systematic review and meta-analysis, study, the prevalence of babesiosis among domestic herbivores in Iran, between 1998 and 2015, was methodically reviewed. Nine databases including five English and four Persian databases were explored. A total of 49 articles, as regards the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
2
9
1
Order By: Relevance
“…Furthermore, the infection rate of B. ovis in the small ruminants of East Azerbaijan, West Azerbaijan, and Razavi Khorasan provinces was 14%, 16.7%, and 0.99%, respectively [ 8 , 21 , 22 ]. In accordance to our findings, a systematic review and meta-analysis on the status of babesiosis in Iran demonstrated that the prevalence of babesiosis in sheep and goats was 21.8% and 10.4%, respectively [ 12 ]. Although it is difficult to compare the results of this and prior studies due to different sample size and various techniques used to identify B. ovis infection, the previous investigations indicate that ovine babesiosis is endemic in different regions of Iran.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the infection rate of B. ovis in the small ruminants of East Azerbaijan, West Azerbaijan, and Razavi Khorasan provinces was 14%, 16.7%, and 0.99%, respectively [ 8 , 21 , 22 ]. In accordance to our findings, a systematic review and meta-analysis on the status of babesiosis in Iran demonstrated that the prevalence of babesiosis in sheep and goats was 21.8% and 10.4%, respectively [ 12 ]. Although it is difficult to compare the results of this and prior studies due to different sample size and various techniques used to identify B. ovis infection, the previous investigations indicate that ovine babesiosis is endemic in different regions of Iran.…”
Section: Discussionsupporting
confidence: 89%
“…The high sensitivity and specificity of molecular methods provide an accurate technique for differentiation of Babesia infections [ 7 , 8 ]. The prevalence of ovine babesiosis in Iran has been studied based on microscopic, serologic, and molecular approaches [ 1 , 9 - 12 ]. In the most of studies in Iran, B. ovis has been reported as the main causative agent of ovine babesiosis [ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…B . ovis is one of the most important and highly pathogenic parasites that infects small ruminants and prevalent in different regions in Iran [9]. Although Rhipicephalus bursa , the tick vector of B .…”
Section: Resultsmentioning
confidence: 99%
“…This method has identified up to 30 species and more than 50 genotypes of Cryptosporidium [6][7][8]. Different species of Cryptosporidium have been reported in various hosts including birds, horses, cattle, sheep, camels, rodents, and dogs.…”
Section: Introductionmentioning
confidence: 99%